Therapeutic modalities and prognostic factors for primary and secondary liver tumors - Lehnert, Thomas; Otto, Gerd; Herfarth, Christian (World journal of surgery, 1995)
During the past decade considerable progress has been reported in the treatment of primary and secondary hepatic malignancies. Refined techniques in surgery, transplantation, radiotherapy, and chemotherapy apparently have made the delivery of treatment safer. At the same time improved understanding of tumor biology has been incorporated in treatment strategies. More recently specific and nonspecific, active and passive immunotherapies have excited wide interest, and information from the first randomized studies is now available. We review current treatment options for primary and secondary hepatic malignancies in an attempt to extract plausible treatment guidelines and to identify promising future directions.
Gesehen am 01.09.2025